LITERATURE REVIEW ON THE USE OF THERAPY OZONE IN MEDICAL AND AESTHETICS - Farahatun Nabilah Mat Isa; Mohd Hafiz Safiai (Journal of Islamic, Social, Economics and Development, 2018)
This article discusses on the usage of ozone therapy as an alternative treatment inmedical and aesthetics. Originally, ozone was used to disinfect bacteria in the operation roomand drinking water treatment before its use is developed for industrial purpose, as well as analternative therapy in treating the chronic illnesses in medicine. However, ozone’s specificationis considered harmful to the patient either in medical field or any other treatment because ofits toxicity. This article purposes to examine the previous studies on the effectiveness of ozonetherapy in medical treatment. Besides, this article also will discusses effects of the therapy onhumans. This article is a qualitative research which is using document analysis approach. Theresults found that although ozone therapy managed to treat various diseases, but it willadversely effect the patient if unsuitable dose used during the therapy. Hence, this articleexpected to disclose and provide knowledge to the patients and medical practitioners inparticular, as well as academicians and public in general about the usage of ozone as a therapyin medical and aesthetics.